The Effect of Using Waqf for Infrastructure and Education on Achieving Sustainable Development Goals in West Java - Judijanto, Loso; Nurnaningsih, Rita; Pahrijal, Rival (Westscience Press, 2024)
This qualitative study investigates the utilization of Waqf for infrastructure and education in achieving Sustainable Development Goals (SDGs) in West Java, Indonesia. Through in-depth interviews with ten stakeholders, including government officials, Waqf administrators, community leaders, educators, and representatives from non-profit organizations, the study explores perceptions, challenges, opportunities, and impacts associated with Waqf-based initiatives. The findings reveal positive perceptions of Waqf as a resource for development, alongside challenges such as regulatory barriers, governance issues, and coordination gaps. Opportunities for leveraging Waqf include public-private partnerships, technology-enabled solutions, innovative financing mechanisms, community engagement, and policy reforms. Despite challenges, Waqf initiatives have contributed to infrastructure development, education provision, poverty alleviation, community empowerment, and environmental sustainability in West Java. The study underscores the need for regulatory reforms, enhanced governance structures, collaboration among stakeholders, technological innovations, and alignment with local development priorities to maximize the impact of Waqf on sustainable development goals.